Critical Analysis of Indonesia’s Cybersecuritization Discourse: Deconstructing the Identification of Securitizing Actors - Kamil Ghiffary A; Hartanto Hartanto; Ivandra Solihin (Politeknik Siber Cerdika Internasional, 2026)
Background: The discussion regarding Securitization Theory in academic literature about state reactions to digital threats is growing alongside the development of Indonesia's digital threat landscape. Yet, this study highlights a methodological shortcoming: existing literature often derives from overly simplistic theories, treating securitization as a mere contextual phenomenon rather than assuming it as an active constructivist frame. Objective: By juxtaposing the structural grammar of the Copenhagen School theory with Myriam Dunn Cavelty’s concept of cybersecuritization, this paper critically engages with recent literature on Indonesia’s cybersecuritization. Methods: Using a qualitative-descriptive Critical Literature Review, this study employs the existing academic discourse as its primary data source, addressing the need to deconstruct two fundamental theoretical building blocks of the concept of securitization—securitizing actors and speech acts. Results: The findings indicate that previous research misapplied the concept of the speech act, taking routine political (locutionary) rhetoric literally and failing to deconstruct its illocutionary intent, contextual purpose, or sequentiality. Moreover, the literature remains grounded in traditional, realist models of